Genetic diversity in cowpea [Vigna unguiculata (L.) Walp.] accessions collected from Togo - Gbedevi, K.M. (Pan African University, 2021)
Cowpea is one of the most widely grown legumes in Togo for its grains and leaves, which are used both as food and feed. Despite its importance in the nutrition and economic life of the people, bulk of the varieties grown in Togo are landraces. Genetic improvement of crops requires the presence of heritable genetic variation. However, there is hardly any information on the extent of variability among cultivated cowpea in Togo. This study was carried out to assess the phenotypic and molecular diversity of some cowpea accessions collected from Togo and to investigate the genetic control of the inheritance of some seed morphological traits in cowpea. Four hundred and ninety-eight accessions of cowpea, which comprised 399 accessions collected from the five administrative regions of Togo: “Region des Savanes” (105 accessions), “Region de la Kara” (98 accessions), “Region Centrale” (50 accessions), “Region des Plateaux” (108 accessions), “Region Maritime” (38 accessions) and 99 accessions from Institut Togolais de Recherche Agronomique (ITRA) were used for this study. The 498 accessions were phenotyped using 35 agronomic and morphological characters, and genotyped using 10,671 DArTseq-based single nucleotide polymorphism (SNP) markers. Multivariate, principal component, and cluster analyses were conducted on phenotypic data, while hierarchical clustering, principal coordinate analysis, analysis of molecular variance, and population structure were carried out on the molecular data. Inheritance of qualitative and quantitative traits were analysed using the chisquare test and generation mean analyses, respectively. Significant variability was observed among the cowpea accessions for the phenotypic traits. The accessions clustered into three and four groups, respectively for the quantitative traits, and both the qualitative and quantitative traits. No cluster is comprised exclusively of accessions from a single region. About 43.1% (4,600) SNP markers were informative. Polymorphic information content among the regions ranged from 0.19 to 0.27 (mean = 0.25). The observed and expected heterozygosities ranged from 0.03 to 0.07 (mean = 0.05) and 0.22 to 0.34 (mean = 0.31), respectively. The average inbreeding coefficient ranged from 0.78 to 0.89 (mean = 0.83), suggesting that most of the accessions are inbred. Cluster analysis and population structure revealed four distinct groups, each containing accessions from six different collecting origins. Differentiation among the populations was weak to moderate, with a genetic differentiation index ranging from 0.014 to 0.117. Within population, variation was the largest (78%), while between population variation was the lowest (7%). Considerable variation was found in the inheritance patterns of the qualitative traits, which in some cases were unique and the expression dependent on the genetic make-up of the parental materials. Additive gene effect controlled the inheritance of seed weight and seed length, while seed width and seed thickness were controlled by a complex of genes, with additive-dominance and epistatic effects. Hundred seed weight and seed length were highly heritable. Moderate level of genetic diversity exists among cowpea accessions from Togo. Mechanisms involved in the inheritance of traits differed, and could depend on parental genotype. The outcomes of this study will be used to improve the genetics of cowpea in Togo.